Management of international construction projects proceedings of a conference organized by the Institution of Civil Engineers and held in London on 14-15 November 1984. (Thomas Telford, 1985)
The focus of these papers highlight turnkey projects, management contracting, the training and involvement of overseas firms, and discuss the Dubai aluminium smelter project.